International Projects and Programs Management - Kukharyk, Viktoriia V. (Lesya Ukrainka Volyn National University, 2021)
The discipline is designed to acquaint students with the features of international project management. The aim of course – to form the appropriate practical skills and abilities in future professionals to use universal tools for the projects development and implementation to achieve effective activity and development of organization. The task of course: to form the appropriate practical skills and abilities in future professionals to use universal tools for the projects development and implementation to achieve effective activity and development of organization.
Keywords: Project; Program; Management